CALCULATIONS OF CURRENT IN THE VUNG RO BAY USING THE FINITE ELEMENT METHOD - Chung, Tran Van; Huan, Nguyen Huu (Vietnam Journal of Marine Science and Technology, 2017)
The analyses the average wind field in the period from 1979 to August 2015 have demonstrated that hydrodynamical processes are dominated by tidal currents in the Vung Ro bay. In this period, the frequency of weak wind accounts for a quite high percentage. Moreover, the wind field is totally influenced by local conditions, and it is less likely to change the speed of tidal currents. The results from a simulation have clearly illustrated that there are similarities between speed and direction in two tidal phases by analyzing the influence of tidal current and the regime of in/out flow in the bay. In addition, the influence of the northeast wind is most obvious at ebb-tide phase, a few small local vortices also appear, notably a local cyclone vortex is located at the north-east of the bay. There are location changes of currents to achieve the maximum value, those velocities increase by around 0.5 cm/s with the clockwise direction of 5.3 degree. The effect of southwest wind has impacted on distribution of currents in flood-tide phase, then the local anticyclonic eddies are formed inside the bay. These eddies have decreased flow rate at a peak point (about 1.7 cm/s) but not prevented the direction and loction of currents from reaching the maximum value (the clockwise direction of less than 0.3 degree)